Composites and metamaterials - Lakes, Roderic (Singapore: World Scientific, 2024)
This book is an excellent primer for students to learn about physical properties, particularly mechanical properties of heterogeneous and multiphase materials and the cultivation of physical insight. Written by a prominent author who pioneered many of the concepts, this book provides a comprehensive coverage of fundamental and current topics in traditional composites and new heterogeneous materials.
Includes appendix and index
Keywords: Composite materials; Metamaterials; Viscoelasticity; Cellular solids